CAPACITY UTILIZATION LEVEL OF FREIGHT ELECTRIC LOCOMOTIVES AND EVALUATION OF EXPENSE REDUCTION ON CONSUMED ENERGY DUE TO MODERNIZATION - Zarifyan, Alexandre; Mustafin, Adel; Valentseva, Elena; Shapshal, Alexandre (Problemy Transportu, 2021)
The working conditions of freight electric locomotives with full-weight and empty-weight trains are analyzed. It is shown that due to the use of scalable traction power control technology (discrete-adaptive control algorithm), there is a possibility for more complete use of electric locomotive capacity and, accordingly, a significant increase in its energy efficiency. The main condition for the realization of this possibility is the presence of an individual per-axle traction control system. Corresponding changes in the construction of electric locomotives of previous years of production can be made during modernization as part of factory repair. The calculation of financial savings from the use of these proposals is presented. Keywords: freight electric locomotive; discrete-adaptive control algorithm; reduction of energy consumption; modernization, locomotive repair plant